Pharmacokinetics of tuberculosis drugs in HIV-infected patients from Irkutsk, Russian Federation: redefining drug activity. Issue 5 (24th May 2018) - Lyles, Galina; Ogarkov, Oleg; Zhdanova, Svetlana; Peloquin, Charles A.; Ebers, Andrew; Pfaeffle, Herman; Al-Shaer, Mohammad H.; Moiseeva, Elena; Zorkaltseva, Elena; Koscheev, Mikhail; Houpt, Eric R.; Heysell, Scott K.
The Russian Federation has the third highest burden of multidrug-resistant (MDR) tuberculosis (TB) in the world, accounting for 10.5% of cases worldwide [1]. Management of the drug-resistant TB epidemic in the Siberian province of Irkutsk is further complicated by high rates of HIV co-infection [2], which leads to early mortality and risk for acquired Mycobacterium tuberculosis drug resistance [3]. Such poor treatment outcomes may be in part a consequence of pharmacokinetic variability rendering subtherapeutic drug concentrations [4–6]. Serum area under the concentration curve (AUC) is the pharmacokinetic parameter correlative with efficacy for most concentration-dependent TB drugs [7, 8] and AUC/minimum inhibitory concentration (MIC) ratio can be further used to predict treatment response [9]. However, relatively few studies have examined the pharmacokinetics of MDR-TB drugs, and none from HIV-infected patients in the Russian Federation. The following prospective cohort study of HIV-TB co-infected patients in Irkutsk was performed to describe pharmacokinetic variability and MIC ranges, and determine if drug activity associates with treatment response. The setting was hypothesised to be particularly informative given the high incidence of MDR- and extensively drug-resistant (XDR)-TB and routine use of novel treatment strategies, including high-dose isoniazid. In Irkutsk, drug concentration testing of TB medications can improve outcomes in HIV-TB co-infected patients http://ow.ly/bj4a30jkqum